Phenotypic and experimental variation in Beauveria bassiana isolates from the Rocky Mountain region - Mann, Andrew, author; Davis, Seth, advisor; Ode, Paul, committee member; Redmond, Miranda, committee member; Stewart, Jane, committee member (Colorado State University. Libraries, 2019)
The ubiquitous insect-killing fungus Beauveria bassiana is widely used as a biological control agent to treat a variety of arthropods ranging from mites to beetles. Dendroctonus rufipennis has been responsible for the death of 17 million Picea engelmannii trees over the past two decades and is currently considered to be one of the major forest pests in western North America. Despite the promise that B. bassiana brings as a form of augmentative biological control against D. rufipennis, a recent laboratory evaluation did not lead to successful field application likely due to a lack of cohesion between environmental conditions that D. rufipennis and B. bassiana prefer. Chapter 1 describes the previous literature on B. bassiana as a biological control agent of Hylesinini bark beetles. In 32 studies to date, not one has studied the pathogenicity of potential strains against a range of abiotic and biotic conditions representative of bark beetle habitats. Therefore, I summarize findings of how B. bassiana might respond to abiotic and biotic factors representative of Hylesinini beetle systems extrapolating from findings in other systems. There is a particular dearth of literature in how B. bassiana responds to competition with other microorganisms and plant secondary metabolites. In chapter 2, I tested 14 B. bassiana isolates from the Rocky Mountain region for their growth, pathogenicity, and virulence in a series of environmental assays representative of the D. rufipennis study system such as a range of temperatures, competition with the spruce beetle symbiotic fungus Leptographium abietinum, constitutive and induced concentrations of five Picea engelmannii monoterpenes, varying levels of osmotic potentials, a nutrient limited environment, and sunlight. Three major findings emerged from this chapter: (1) genetically related B. bassiana isolates from similar habitats and sources exhibit considerable variation in their growth response to environmental conditions; (2) low temperatures and monoterpenes are highly inhibitory to B. bassiana growth, pathogenicity, and virulence; and (3) the interpretation of isolate virulence and pathogenicity can differ substantially depending on bioassay design. These collective findings have implications for the field application of B. bassiana as a bark beetle control agent and could help explain discrepancies between laboratory field assessments.